(untitled) (Itinera, 2020)
«Why has the examination of many different aspects of colour been a prominent feature in philosophy, to such an extent that the topic is worthy of a handbook?». This is the question that opens the editors’ introduction to The Routledge Handbook of Colour, whose imminent publication we are happy to announce here.